Prosody and discourse (Eurasian Journal of Philology Science and Education, 2016)
The article shares the role of prosody in human life and the process of communication. The content of the concept «prosody» is studied and their similarities and differences are considered. On the basis of the explanations and definitions given to the term in the researches of the scientists of the Kazakh, Russian and English languages, there was made an attempt to describe the concepts «prosody», «prosodics» and «intonation». In the result of this, language units: intoneme and prosodeme, differentiating these phenomena from each other are defined. The prosody and intonation and their functions in communication are investigated in the article. The author considers the role of prosody in a discourse and the level of research of the issue. The works of many scientists of the phenomenon prosody in a discourse and speech and its function are reviewed. There isn’t still formed a common opinion on the definition of «discourse» and one of the lots of reasons for this must be the manysidedness of discourse in the study.
Keywords: prosody; discourse; intonation; function of prosody; aca¬demic discourse; prosodics